The Role of Artificial Intelligence in Personalized Learning - Dr. Yad Ram (Innovative Research Thoughts, 2025)
By providing individualized, data-driven, and adaptable learning experiences for each learner, artificial intelligence (AI) is revolutionizing the conventional educational landscape. This study examines how artificial intelligence (AI) is helping to support personalized learning, which uses clever algorithms and systems to suit a range of learning preferences, styles, and speeds. Artificial intelligence (AI) tools like machine learning, natural language processing, and learning analytics enable teachers and learning platforms to evaluate students' progress in real time, spot learning gaps, and offer personalized feedback and information. Through the promotion of a student-centric approach to education, these capacities greatly increase learner engagement, motivation, and achievement. The study also examines a number of AI-powered tools that are currently being used in educational contexts, such as predictive analytics, adaptive learning platforms, and intelligent tutoring systems. The efficiency and expanding use of these technologies are demonstrated by case studies from K–12 educational institutions, colleges, and corporate training initiatives. Additionally, the study explores how AI can support inclusive education, lessen the strain for teachers, and create chances for lifelong learning.